Efficacy and Safety of Vasopressin Receptor Antagonists for Euvolemic or Hypervolemic Hyponatremia: A Meta-Analysis. Issue 15 (April 2016) - Zhang, Xiangyun; Zhao, Mingyi; Du, Wei; Zu, Dongni; Sun, Yingwei; Xiang, Rongwu; Yang, Jingyu
Abstract : Abstract: Hyponatremia, defined as a nonartifactual serum sodium level <135 mmol/L, is the most common fluid and electrolyte abnormality in clinical practice. Traditional managements (fluid restriction, hypertonic saline and loop diuretics, etc.) are difficult to maintain or ineffective. Recently, vasopressin receptor antagonists (VRAs) have shown promise for the treatment of hyponatremia. We aimed to conduct a meta-analysis to evaluate the efficacy and safety of VRAs in patients with euvolemic or hypervolemic hyponatremia. We searched Pubmed, Cochrane Library, Web of Science and Springer, etc. (latest search on June 4, 2015) for English publications with randomized controlled trials. Two authors independently screened the citations and extracted data. We calculated pooled relative risk (RR), risk difference (RD), weighted mean difference (WMD) or standard mean difference (SMD), and 95% confidence intervals (CIs) by using random and fixed effect models. We collected data from 18 trials involving 1806 patients. Both random and fixed effect meta-analyses showed that VRAs significantly increased the net change of serum sodium concentration (WMDrandom  = 4.89 mEq/L, 95%CIs = 4.35–5.43 and WMDfixed  = 4.70 mEq/L, 95%CIs = 4.45–4.95), response rate (RRrandom  = 2.77, 95%CIs = 2.29–3.36 and RRfixed  = 2.95, 95%CIs = 2.56–3.41), and 24-hour urine output (SMDrandom  = 0.82, 95%CIs = 0.65–1.00 and SMDfixed  = 0.79, 95%CIs = 0.66–0.93) compared to placebo. Furthermore, VRAs significantly decreased body weight (WMDrandom  = −0.87 kg, 95%CIs = −1.24 to −0.49 and WMDfixed  = −0.91 kg, 95%CIs = −1.22 to −0.59). In terms of safety, rates of drug-related adverse events (AEs), rapid sodium level correction, constipation, dry mouth, thirst, and phlebitis in the VRA-treated group were greater than those in control group. However, there was no difference in the total number of AEs, discontinuations due to AEs, serious AEs, death, headache, hypotension, nausea, anemia, hypernatremia, urinary tract infection, renal failure, pyrexia, upper gastrointestinal bleeding, diarrhea, vomiting, peripheral edema, and dizziness between the 2 groups. Random effect meta-analyses showed that post treatment urine osmolality, supine systolic blood pressure, and diastolic blood pressure were lowered (WMDrandom  = −233.07 mOsmol/kg, 95%CIs = −298.20–147.94; WMDrandom  = −6.11 mmHg, 95%CIs = −9.810 to −2.41; WMDrandom  = −2.59 mmHg, 95%CIs = −4.06 to −1.11, respectively), but serum osmolality was increased (WMDrandom  = 9.29 mOsmol/kg, 95%CIs = 5.56–13.03). There was no significant change from baseline in serum potassium concentration between the 2 groups (WMDfixed  = 0.00 mmHg, 95%CIs = −0.07–0.06). VRAs are relatively effective and safe for the treatment of hypervolemic and euvolemic hyponatremia.